Factors influencing the measurement of pleural fluid pH. - Mishra, E; Rahman, N (2009)
PURPOSE OF REVIEW: Pleural fluid pH measurement is important in the management of patients with exudative pleural effusions, especially in guiding treatment of parapneumonic effusions. Common variations in the method used to sample pleural fluid affect the accuracy of the value obtained. This article reviews the effects of these variations. RECENT FINDINGS: Pleural fluid pH is decreased by exposure to acidic fluids, such as retention of local anesthetic or heparin in the syringe or sampling following infiltration of local anesthetic. Exposure of the sample to air leads to an increase in pH. If immediate analysis is not possible, delay of up to 4 h does not cause a significant change in pH, even when the sample is kept at room temperature. It is essential that a blood gas analyzer is used to obtain accurate pH measurement.These factors have less effect on the glucose concentration, which may be used to guide management if an accurate pH value is not available. SUMMARY: Several common variables in collection method can lead to a clinically significant alteration in the pH value obtained. An evidence-based method for sampling and handling pleural fluid in order to obtain an accurate pH measurement is described.